2019
DOI: 10.1007/s00109-019-01763-3
|View full text |Cite|
|
Sign up to set email alerts
|

PRSS21/testisin inhibits ovarian tumor metastasis and antagonizes proangiogenic angiopoietins ANG2 and ANGPTL4

Abstract: Ovarian cancer is the leading cause of death among all the gynecological cancers in the United States. Ovarian cancer employs a unique mode of metastasis, as exfoliated tumor cells disseminate within the peritoneal cavity, colonizing in several sites as well as accumulating ascites. Tumor recurrence and widespread metastasis are significant factors contributing to poor prognosis. PRSS21 is a metastasis associated ovarian cancer gene that encodes the glycosylphosphatidylinositol-linked serine protease, testisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
(71 reference statements)
0
26
0
Order By: Relevance
“…Silencing ANGPTL4 reduces A2780 and CAOV3 tumor growth, angiogenesis, and metastasis in vivo but not in vitro, indicating that ANGPTL4 is essential for tumor proliferation and vascular angiogenesis in ovarian cancer. However, several studies have claimed that ANGPTL4 inhibits vascular angiogenesis and prevents tumor metastasis in melanoma B16F0, lung cancer 3LL [ 10 ] and colon cancer CMT93 [ 9 ] xenograft mouse models; however, contrasting results were observed in breast cancer [ 11 ], renal cell carcinoma [ 14 ], and ovarian cancer [ 16 , 17 ] xenograft models, indicating that ANGPTL4 may act as a tissue-specific and multifunctional vascular modulator. Furthermore, previous studies have shown that two proteins, PDZ-binding motif (TAZ) and testisin, inhibit ovarian cancer metastasis and that ferroptosis and chemoresistance are also related to ANGPTL4 inhibition [ 16 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing ANGPTL4 reduces A2780 and CAOV3 tumor growth, angiogenesis, and metastasis in vivo but not in vitro, indicating that ANGPTL4 is essential for tumor proliferation and vascular angiogenesis in ovarian cancer. However, several studies have claimed that ANGPTL4 inhibits vascular angiogenesis and prevents tumor metastasis in melanoma B16F0, lung cancer 3LL [ 10 ] and colon cancer CMT93 [ 9 ] xenograft mouse models; however, contrasting results were observed in breast cancer [ 11 ], renal cell carcinoma [ 14 ], and ovarian cancer [ 16 , 17 ] xenograft models, indicating that ANGPTL4 may act as a tissue-specific and multifunctional vascular modulator. Furthermore, previous studies have shown that two proteins, PDZ-binding motif (TAZ) and testisin, inhibit ovarian cancer metastasis and that ferroptosis and chemoresistance are also related to ANGPTL4 inhibition [ 16 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the transforming growth factor-beta 2 (TGF-β2)/ANGPTL4 axis was reported to be responsible for breast cancer brain metastasis in a mouse model [ 15 ]. Previous studies reported that high ANGPTL4 expression was detected in ovarian cancer xenograft mouse models and patients and was associated with shorter relapse-free survival times in serous ovarian carcinoma [ 16 , 17 ]. However, whether ANGPTL4 deletion has clinical benefit in ovarian cancer therapy is unknown, and the related molecular mechanisms are obscure.…”
Section: Introductionmentioning
confidence: 99%
“…[49] Moreover, large amounts of it has been detected in malignant ascites of serous OV patients. [50] High ANGPTL4 levels predict shorter relapse-free survival in serous OV. [50,51] Studies have found that high promoter hypermethylation of TGFBI (transforming growth factor-beta-inducible gene) is involved in chemotherapy resistance of paclitaxel in OV.…”
Section: Discussionmentioning
confidence: 99%
“…(50) High ANGPTL4 levels predict shorter relapse-free survival in serous OV. (50,51) Studies have found that high promoter hypermethylation of TGFBI (transforming growth factor-beta-inducible gene) is involved in chemotherapy resistance of paclitaxel in OV. (52,53) A study showed that TGFBI and periostin, predict poor prognosis in serous epithelial OV.…”
Section: Discussionmentioning
confidence: 99%